2015
DOI: 10.1097/aco.0000000000000153
|View full text |Cite
|
Sign up to set email alerts
|

Dead space during one-lung ventilation

Abstract: Monitoring dead space helps anesthesiologists monitor the status of the lung and find appropriate ventilatory settings during thoracic surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Observation indicators: Qs/Qt(%), OI, PaCO 2 at T 1 , T 2 , T 3 , T 4 and T 5 ; P peak , P plat and Cdyn at T 1 , T 2 and T 3 ; the concentrations of IL-6 and TNF-α in venous blood at T 1 and T 5 ; clinical pulmonary infection score (CPIS) at the 1st day and 7th day after the operation (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observation indicators: Qs/Qt(%), OI, PaCO 2 at T 1 , T 2 , T 3 , T 4 and T 5 ; P peak , P plat and Cdyn at T 1 , T 2 and T 3 ; the concentrations of IL-6 and TNF-α in venous blood at T 1 and T 5 ; clinical pulmonary infection score (CPIS) at the 1st day and 7th day after the operation (21).…”
Section: Methodsmentioning
confidence: 99%
“…During OLV, solely small tidal volume ventilation cannot decrease the occurrence of sheering injury of the lungs, which is close to alveolar trapping and re-expansion (6,21). Fernandez-Bustamante et al (16) noted that for obese patients with OLV, the ventilation-side lung more easily suffered from atelectasis, and that positive end-expiratory pressure (PEEP) was the most effective approach to keep the alveoli open, which could reduce the collapse of the alveoli (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In constant dead space volume given (VDaw), alveolar ventilation could vary significantly with changing frequency and amplitude, while minute ventilation will remained constant [4,5]. Measurements of alveolar and anatomical dead space volumes were problematic that prevented from using them in clinical practice [9,10] However, recent achievements in socalled volumetric capnography (VCap) and better understanding of its clinical impact helped in overcoming restrictions related to the CO 2 flow and the dead space [11,12]. At present, we are able to measure the dead space at the bedside.…”
Section: материал и методыmentioning
confidence: 99%
“…При заданном постоянном объеме мертвого пространства (Vdaw) альвеолярная вентиляция может значительно различаться при изменении частоты и амплитуды дыхания, тогда как минутная вентиляция легких остается неизменной [4,5]. Сложность измерения объемов альвеолярного и анатомического мертвого пространств представляло проблему, не позволявшую широко использовать эти данные в клинической практике [9,10]. Однако, использование так называемой объемной капнографии (VCap) и лучшее понимание ее клинического значения помогли преодолеть ограничения, связанные с оценкой потока CO 2 и объема мертвого пространства [11,12].…”
Section: Introductionunclassified
“…Tusman et al [ 49 ] showed that the highest pulse oximetry oxygen saturation (SpO 2 ), the lowest VD and the highest VTCO 2 ,br (CO 2 production per breath) occur at the PEEP level that keeps alveoli open. They also studied patients undergoing one-lung ventilation (OLV) during thoracic surgery [ 50 ]. In thoracic surgery one of the main goals of anesthesiologists is to maintain adequate minute ventilation while keeping tidal volume below a level that over-distends dependent lung units and produces VD and lung injury.…”
Section: Others Applications Of Vcapmentioning
confidence: 99%